Successful Of Embolization Therapy On Recurrent Massive Hemoptysis because of TB Sequelae - Merdekawati, Ratih Dwi ary; Pratiwi, Suryanti Dwi; Bayhaqi, Ahmad (Universitaas Brawijaya, 2020)
AbstractBackground: Haemoptysis is one of vascular lesions in TB sequelae, with incidence of 28% from 919 cases. It may be recurrent, massive and might cause mortality if left untreated. Embolization procedure with glue and coil can be an alternative to treat patient with recurrent hemoptysis.Case Report: We reported a case report in Saiful Anwar Malang Hospital, Indonesia, a 34 years old male with intermittent massive haemoptysis. Chest X-ray examination showed Lung Tb far advanced lesion with no acid bacilli found on microbiological examination. Transthoracic FNAB revealed chronic suppurative inflammation, with Cytology sputum Class II. Chest CT Angiography showed Lung TB Far advanced lesions accompanied by mediastinal lymphadenopathy with unsuspecting complications of left supreme intercostal artery aneurysm dd pseudoaneurysm, suggestion embolization. Examination results confirmed the diagnosis of recurrent massive haemoptysis and intercostal artery aneurysm with the history of TB. Embolization procedure was then performed.Conclusion: Angiography CT Scan has better detail in evaluating condition, source, amount, and tract of artery in chest cavity. Bronchial artery embolization as an alternative therapy was found to give better effect of occlusion.Keywords: Massive haemoptysis, chest CT angiography, embolization.